PENGARUH KEPEMIMPINAN DAN KOMUNIKASI INTERPERSONAL TERHADAP KINERJA KARYAWAN (Studi Pada Karyawan Bagian Produksi PT. Cahaya Kharisma Plasindo Cabang Grogol, Sukoharjo) - Sinta Listiarini Putri; Apriatni Endang Prihatini (Jurnal Ilmu Administrasi Bisnis, 2017)
Employee performance is influenced by many factors including leadership and interpersonal communication. PT. Cahaya Kharisma Plasindo Grogol Branch Office, Sukoharjo on its production activities have production targets so it requires capable production leaders and interpersonal communication that is well established to improve the performance of production employees. The problem in this research is the decrease of employee performance of production by an increase in the number of defective product during last 4 years.The study aims to determine the effect of leadership and interpersonal communication on employee performance an production sector PT. Cahaya Kharisma Plasindo Grogol Branch Office, Sukoharjo. This type of research is explanatory. Data collection through a questionnaire, interview and literature study. Sample of this research is all employees of production department PT. Cahaya Kharisma Plasindo Grogol Branch Office, Sukoharjo which amounts to 96 people. Measurement scale using Likert Scale. data analysis using validity and reability, simple and multiple regression analysis, the coefficient of determination and correlation, significance test (t test and F test) with the help of SPSS software version 16.0.The result from data analysis concluded that leadership has a significant influence on employee performance. interpersonal communication has a significant influence on employee performance. Leadership and interpersonal communication are equally has a significant influence on employee performance.Based on the results, suggested in a attempt to improve employee performance of part production, production manager should get attention to the practice of leadership by giving command clearly and slowly about what the employee must do and briefing how to use the machine correctly. Interpersonal communication production manager with his employees needs to be noticed by empathizing with his employees and be positive by paying attention to what the employees say.